Solutions for Small Farmers and Home Gardens: Building a Low-Cost Vertical Soilless System for Production of Small Vegetable and Fruit Crops - Bielinski M. Santos; Teresa P. Salame-Donoso; Shawn C. Arango (EDIS)
HS1186, a 5-page illustrated fact sheet by Bielinski M. Santos, Teresa P. Salame-Donoso, and Shawn C. Arango, provides written and graphic instructions on how to build a homemade vertical soilless (hydroponic) growing system (also known as “bottle grow”) to produce vegetables and small fruit crops at a fraction of the cost of commercially available systems, without occupying premium agricultural land and by utilizing materials available in the home and local hardware store. Published by the UF Department of Horticultural Sciences, November 2010.